Overweight and Obesity: Risk Factors in Calcium Oxalate Stone Disease? - Beate Maria Wrobel; Gernot Schubert; Markus Hörmann; Walter Ludwig Strohmaier (Advances in Urology)
Introduction. Several studies showed an association of overweight and obesity with calcium oxalate stone disease (CaOx). However, there are no sufficient data on the influence of body weight on the course of the disease and the recurrence rate. Patients and Methods. N=100 consecutive stone formers with pure CaOx were studied. Different parameters were investigated. According to the BMI, patients were divided into three groups: (1) BMI≤25; (2) BMI 25.1–30; (3) BMI>30. Results. N=32 patients showed a BMI≤25, n=42 patients showed a BMI of 25.1–30 and n=26 patients showed a BMI≥30. The groups differed significantly concerning BMI (by definition), urine pH, and urine citrate. The recurrence rate was not significantly different. Discussion. Our study demonstrated that body weight negatively influences single risk factors in CaOx, but obesity is not a predictor for the risk of recurrence in CaOx.